2008
DOI: 10.1007/s00520-008-0494-1
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of cancer coverage in important Chinese newspapers between 2000 and 2007

Abstract: In the past eight years, Chinese main newspapers have significantly increased the number of cancer-related reports and paid more attention to women's cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 8 publications
7
10
0
Order By: Relevance
“…That breast cancer dominates media coverage in newspapers as well as magazines, television news broadcasts and online news is a consistent finding with previous research 6 8 9 20–23. It has been suggested that this is likely to be due to the early establishment and effective marketing models used by breast cancer campaigners 7 24.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…That breast cancer dominates media coverage in newspapers as well as magazines, television news broadcasts and online news is a consistent finding with previous research 6 8 9 20–23. It has been suggested that this is likely to be due to the early establishment and effective marketing models used by breast cancer campaigners 7 24.…”
Section: Discussionsupporting
confidence: 90%
“…Lung cancer was the second most commonly reported cancer in this study, consistent with other analyses of newspaper coverage 6 9. Other studies have also found that this cancer was heavily under-represented, considering its high incidence and mortality rate 6–8.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results indicate a tendency of increasing coverage about skin cancer from 2000 through 2007, consistent with our previous study about cancer coverage, which also showed an increasing tendency (Cai, Yang, Liu, & Liu, 2009). We found a sharp increase in 2006.…”
Section: Discussionsupporting
confidence: 93%
“…The total number of articles related to cancer during this same period was 7,643 (Cai, Yang, Liu, & Liu, 2009); thus, skin cancer articles represented about 1.8% (n = 134) of all articles that were cancer related.…”
Section: Resultsmentioning
confidence: 99%